Advisory opinion of the International Court of Justice on the accordance with international law of the unilateral declaration of independence in respect of Kosovo (2011)
Este documento contiene en texto completo el articulo Advisory opinion of the International Court of Justice on the accordance with international law of the unilateral declaration of independence in respect of Kosovo publicado en ACDI - Anuario Colombiano de Derecho Internacional; Vol. 4 (2011): ACDI; 243-308;Annuaire Colombien de Droit International - ACDI; Vol. 4 (2011): ACDI; 243-308;Colombian Yearbook of International Law - CYIL; Vol. 4 (2011): ACDI; 243-308;2145-4493;2027-1131